Pretreatment with Retro‐2 protects cells from death caused by ricin toxin by retaining the capacity of protein synthesis. Issue 10 (30th May 2020) - Jiao, Zhouguang; Ke, Yuehua; Li, Sha; Su, Duo; Gan, Changjiao; Hu, Lingfei; Zhao, Xiaodong; Gao, Bo; Song, Yajun; Zhou, Dongsheng; Qiu, Yefeng; Yang, Huiying
Abstract: The current study explores the detoxification effect of Retro‐2 on ricin toxin (RT) cytotoxicity, as well as the mechanisms underlying such effects, to provide a basis for follow‐up clinical applications of Retro‐2. The mouse‐derived mononuclear/macrophage cell line, RAW264.7, was used to evaluate the detoxification effect of Retro‐2 on RT by detecting cell viability, capacity for protein synthesis and the expression of cytokines, as well as endoplasmic reticulum stress (ERS)‐related mRNA. The results indicated that many cells died when challenged with concentrations of RT ≥50ng/mL. The protein synthesis capacity of cells decreased when challenged with 200ng/mL RT for 2hours. Furthermore, the synthesis and release of many cytokines decreased, while the expression of cytokines or ERS‐related mRNA increased when challenged with 200ng/mL of RT for 12 or more hours. However, cell viability, capacity for protein synthesis and release levels of many cytokines were higher, while the expression levels of cytokine, or ERS‐related mRNA, were lower in cells pretreated with 20μm Retro‐2 and challenged with RT, compared with those that had not been pretreated with Retro‐2. In conclusion, Retro‐2 retained the capacity for protein synthesis inhibited by RT, alleviated ERS induced by RT and increased the viability of cells challenged with RT. Retro‐2 shows the potential for clinical applications. Abstract : The current study explores the detoxification effect of Retro‐2 on ricin toxin (RT) cytotoxicity, as well as the mechanisms underlying such effects. The RAW264.7 cells was used to evaluate the detoxification effect of Retro‐2 on RT. The results indicated that cell viability, capacity for protein synthesis and release levels of many cytokines were higher, while the expression levels of cytokine, or endoplasmic reticulum stress (ERS)‐related mRNA, were lower in cells pretreated with 20μm Retro‐2 and challenged with RT, compared with those that had not been pretreated with Retro‐2. In conclusion, Retro‐2 retained the capacity for protein synthesis inhibited by RT, alleviated ERS induced by RT and increased the viability of cells challenged with RT. Retro‐2 shows the potential for clinical applications.